Identita' e lingua di madri moldave emigrate in Italia - Nutricato, Mariacristina; Ferraresi, Paola; Fantasia, Valentina; Bello, Arianna (Journal of Educational, Cultural and Psychological Studies, 2023)
The present study investigates family-related language practices of Moldovan mothers emigrated to Italy, through a semi-structured interview. To date, few studies have considered linguistic choices in relation to educational practices and identity aspects in this population. Ten Moldovan woman have been interviewed. Results from a thematic analysis on the collected interviews has highlighted a complex relationship between identity, language and education: the use of the mother tongue or the «new» language appeared intertwined with the historical and political events of the country of origin, with consequences on the different use of languages in domestic contexts, through specific choices or «code-mixing»; or in extended family contexts. With their children, the language of origin is predominant, although the practices adopted to promote it are often mediated by TV. Overall, the findings confirm the interdependent nature of the cultural, social and identity aspects that influence language practices in migrant families from Moldova; at the same time, the selective use of these practices within different contexts and relationships has consequences for their children’s educational experiences.
Keywords: educazione; Migrazione e identità moldava; Pratiche linguistiche in famiglia; Ricerca qualitativa; Education; Family language practices; Moldovan migration and identity; Qualitative research